2019
DOI: 10.1007/s00134-019-05620-2
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin in septic shock: an individual patient data meta-analysis of randomised controlled trials

Abstract: We performed an individual patient data meta-analysis to investigate the possible benefits and harms of vasopressin therapy in adults with septic shock both overall and in pre-defined subgroups. Methods: Our pre-specified study protocol is published on PROSPERO, CRD42017071698. We identified randomised clinical trials up to January 2019 investigating vasopressin therapy versus any other vasoactive comparator in adults with septic shock. Individual patient data from each trial were compiled. Conventional two-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 38 publications
2
66
1
3
Order By: Relevance
“…This meta-analysis underlined the additional risk of digital ischaemia [51]. In a recent meta-analysis of individual patients data from randomized studies (1453 septic shock patients) [52], no difference in mortality was found between vasopressin and norepinephrine. Furthermore, vasopressin use was not associated with more undesirable effect, but safety profiles were different: vasopressin led to more digital ischaemia, but fewer arrhythmias.…”
Section: Vasopressin Analogues: Terlipressin and Selepressinmentioning
confidence: 91%
“…This meta-analysis underlined the additional risk of digital ischaemia [51]. In a recent meta-analysis of individual patients data from randomized studies (1453 septic shock patients) [52], no difference in mortality was found between vasopressin and norepinephrine. Furthermore, vasopressin use was not associated with more undesirable effect, but safety profiles were different: vasopressin led to more digital ischaemia, but fewer arrhythmias.…”
Section: Vasopressin Analogues: Terlipressin and Selepressinmentioning
confidence: 91%
“…The use of noradrenalin as compared to vasopressin (the endogenous hormone arginine-vasopressin, which is shorter acting than terlipressin) will likely result in more episodes of atrial fibrillation as observed in a recent IPDMA [14]. Also, in this analysis, more episodes of digital ischemia were observed with vasopressin as compared to noradrenalin.…”
mentioning
confidence: 71%
“…In a Chinese randomised clinical trial of 617 patients with septic shock, no difference in mortality between patients receiving terlipressin versus norepinephrine was observed; however, patients in the terlipressin group experienced more serious adverse events [15]. In a recent individual patient data meta-analysis of four RCTs, the use of vasopressin in patients with septic shock reduced arrhythmias, on the expense of a small increase in the risk of digital ischemia compared to norepinephrine [16].…”
mentioning
confidence: 99%